Genomic analysis of a cAmpC (CMY-41)-producing Citrobacter freundii ST64 isolated from patient - Monte, Daniel F.M.; Gonzalez-Escalona, Narjol; Cao, Guojie; Targino de Souza Pedrosa, Geany; Saraiva, Mauro M.S. [UNESP]; Balkey, Maria; Jin, Qing; Brown, Eric; Allard, Marc; Macarisin, Dumitru; Magnani, Marciane (Oxford University Press (OUP), 2024)
Antibiotic resistance in Citrobacter freundii is a public health concern. This study evaluated the closed genome of a C. freundii isolated from the stool of a hospitalized patient initially related to a Salmonella outbreak. Confirmation of the isolate was determined by whole-genome sequencing. Nanopore sequencing was performed using a MinION with a Flongle flow cell. Assembly using SPAdes and Unicycler yielded a closed genome annotated by National Center for Biotechnology Information Prokaryotic Genome Annotation Pipeline. Genomic analyses employed MLST 2.0, ResFinder4.1, PlasmidFinder2.1, and VFanalyzer. Phylogenetic comparison utilized the Center for Food Safety and Applied Nutrition (CFSAN)single nucleotide polymorphism pipeline and Genetic Algorithm for Rapid Likelihood Inference. Antimicrobial susceptibility was tested by broth microdilution following Clinical and Laboratory Standards Institute criteria. Multi-locus sequence type in silico analysis assigned the C. freundii as sequence type 64 and the blaCMY-41 gene was detected in resistome investigation. The susceptibility to antibiotics, determined using Sensititre® plates, revealed resistance to aztreonam, colistin, cefoxitin, amoxicillin/clavulanic acid, sulfisoxazole, ampicillin, and streptomycin. The genetic relatedness of the C. freundii CFSAN077772 with publicly available C. freundii genomes revealed a close relationship to a C. freundii SRR1186659, isolated in 2009 from human stool in Tanzania. In addition, C. freundii CFSAN077772 is nested in the same cluster with C. freundii clinical strains isolated in Denmark, Mexico, Myanmar, and Canada, suggesting a successful intercontinental spread.